Direct growth and Photoluminescence of SiOx nanowires and aligned nanocakes by simple carbothermal evaporation - Al-Ruqeishi, M.S.; Nor, R.M.; Amin, Y.M.; Al-Azri, K. (2011)
The growth of SiOx nanowires and nanocakes on an Au-coated n-type-Silicon (100) substrate was achieved via carbothermal evaporation. The effects of the Au layer thickness and the rapid heating rate on the morphology of obtained SiOx nanowires were investigated. A broad emission band from 290 to 600 nm was observed in the photoluminescence (PL) spectrum of these nanowires. There are four PL peaks: one blue emission peak 485 nm (2.56 eV) two green bands centered at 502 nm (2.47 eV) and 524 nm (2.37 eV) for nanocakes and one ultraviolet emission peak at 350 nm (3.54 eV) and a hemisphere curve over the bluish green area taken for SiOx nanowires. These emissions may be related to the various oxygen defects and twofold coordinated silicon lone pair centers.